Photoalignment of liquid crystal in photonic crsytal fiber by using azo dye. - Peck, Yvonne. (2011)
Photonic Crystal Fibers (PCFs) have emerged to be a new class of optical waveguides, which have attracted considerable attention and interest in recent years. PCFs are microstructured waveguides, conventionally made up of silica. They have a large number of air holes located within the cladding region of the fiber. The presence of air holes in the PCF provides a close contact to the fiber core. Thus, by infiltrating new materials into the air holes, a high degree of interaction between light and the material can be achieved and at the same time, maintaining the microstructure of the fiber. However, these micron sized structures impose a problem in the modulation of LC alignment in the air holes.